Numerical investigations on feasibility of Quasi MR-Process for 2-valve diesel engines - Calik, Alper Tolga; Taskiran, Ozgur Oguz; Mehdiyev, Rafig (Elsevier Sci Ltd, 2018)
MR-Process consists two stage combustion mechanism in twin swirl flow conditions which is created by special design of 2 intake manifolds and combustion chamber (CC) geometry of a 4-valve engine. It is a question if it is possible to apply a Quasi MR-Process by modifying CC of a 2-valve engine which has only one intake manifold. Previously engine tests were successfully conducted on a 2-valve and modified CC (MR-2 CC) single cylinder test engine with one intake manifold using LPG and diesel fuels. Nevertheless because of there is no optical access inside the engine, it is not clear whether required twin swirl flow (to create Quasi MR-Process) occurs inside CCs of proposed 2-valve engines. In this study, our aim is to improve the clarification of the swirl motion and air-fuel mixture formation for said Quasi MR-Process CC application in 2-valve diesel engines. Two different CC geometries were investigated in terms of Quasi MR-Process generation potential by using KIVA3V-R2 code. CFD predictions of air flow motion, air-fuel mixture formation and diesel spray combustion were analyzed and compared with each other in a methodical manner. The results showed that 2 valve engine CC is not capable of creating optimal twin swirl. However, it is presented that generation of twin swirl can be improved by application of modified (MR-2 CC) piston head design.
Keywords: Air-fuel mixture formation; MR-Process; Twin swirl; Numerical analysis